The Effect of Innovation and Product Quality on Consumer Satisfaction In Coconut Charcoal Products CV. Superior Agro - Fadillah, Muhammad Rizky; Ubaidillah, Ahmad Zulfahmi; Ratnawati, R. Aryanti; Acuviarta, Acuviarta (Adpebi Science Series, 2022)
This study is motivated by the use of energy that is used continuously every time will result in the depletion of the energy. Coconut charcoal can be an alternative solution to replace the role of non-renewable energy. CV. Superior Agro as one of the producers of coconut charcoal. The problem discussed in this article is the decline in sales from January to December 2021 due to a decrease in consumer satisfaction with CV. coconut charcoal products. Superior Agro. This study was conducted to analyze how much influence innovation and product quality have on consumer satisfaction on CV coconut charcoal products. Superior Agro. The object of this research is a coconut charcoal product CV. Superior Agro. This study uses associative and descriptive methods with a quantitative approach, namely research that aims to determine the effect between two or more variables, with quantitative research in the form of description using numbers or numerical (statistics). The number of samples obtained from calculations using the solvin formula is 72.75 and is rounded up to 73 samples. Based on the analysis using SPSS, respondents' responses regarding innovation have the highest score, which is 3.78. Respondents' responses regarding product quality have the highest score of 3.88. Meanwhile, respondents' responses regarding customer satisfaction have the highest value, namely 3.68. The result is known that the variables of Product Quality and Innovation have a significant influence together on the Consumer Satisfaction variable. These results are supported by the results of research and tests that have been carried out.